Finanzas presupuestales y la gestión por objetivos del proyecto Marca Loreto del Gobierno Regional de Loreto, Iquitos - periodo 2022 - Ramos Vasquez, Karen (2023)
The objective of this research work was to evaluate how budgetary finances are related to the management by objectives of the Loreto Brand Project of the Loreto Regional Government, Iquitos- period 2022, with a quantitative research type of non-experimental design and type correlational cross-sectional design; with a study population made up of 31 workers from the Economic Development Management of the Loreto Regional Government, in addition to analyzing the reports of budget execution in physical and financial goals of the Loreto brand, using documentary analysis as instruments. and survey; concluding that the general hypothesis is accepted since in the results the statistical value "r" of Pearson is 0.763, being a very significant correlation given that the value of Sig. (bilateral) is less than 0.01; so it can be said that it has a 99% confidence level; In addition, in the field of study there is a high correlation between the Budgetary Finance and Management by Objectives variable, since the degree of correlation is in the range of 0.60-0.79 (high correlation), of the 04 components that the brand only 01 component has a physical progress of 63.63% and 03 components do not exceed 22%, with respect to financial progress the 04 components mentioned do not exceed 45% of execution.